Daidzein Alleviates Hypothalamic-Pituitary-Adrenal Axis Hyperactivity, Ameliorates Depression-Like Behavior, and Partly Rectifies Circulating Cytokine Imbalance in Two Rodent Models of Depression - Chen, Long; Wang, Xiaokun; Zhang, Yunpeng; Zhong, Hequan; Wang, Cuiting; Gao, Pengfei; Li, Bing (Frontiers in Behavioral Neuroscience, 2021)
Depression is one very common mental health disorder which can cause morbidity and mortality if not addressed. Recent studies have provided strong evidence that depression may be accompanied by immune activation, secondary inflammatory reaction, and hyperactivity of the Hypothalamic Pituitary Adrenal (HPA) axis. It is well-known that it takes at least 2 weeks for conventional antidepressants, especially SSRIs (Selective serotonin reuptake inhibitors) to produce effects. To better understand the mechanism of antidepressant effects on depression and subsequently further elucidate the pathogenesis of depression, we selected phytestrogen daidzein (DD) to observe its effects on the depression-like and anxiety-like behavior in two different rodent models of depression which were induced by learned helplessness and chronic mild stress (CMS) and then simultaneous evaluation of the depression-like behavior, the activity of HPA axis, and circulatory cytokines. Our results showed that daidzein attenuated depression-like behaviors through alleviating HPA axis hyperactivity, decreasing the levels of stress-related hormones, and partly rectifying some inflammatory cytokines imbalance in both the rodent models of depression.